2021
DOI: 10.1155/2021/5573839
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Retinal Structure and Optic Nerve Function Changes in Multiple Sclerosis: Longitudinal Study with 1-Year Follow-Up

Abstract: Background. Multiple sclerosis (MS) is an autoimmune disease characterized by inflammation and demyelination of the central nervous system which often involves the optic nerve even though only 20% of the patients experience optic neuritis (ON). Objective. This study aims to compare the retinal structure and optic nerve function between patients with MS and healthy controls (HCs), evaluate optic nerve alterations in MS over 1-year follow-up, and analyze its correlations with disease duration, number of relapses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…However, in studies of patients with MS, the optic nerve has been described to appear pale and atrophied, and patients with Parkinson's have been shown to have shallower cups compared to healthy controls. 39 , 40 Additionally, optic nerve pallor, increased CDR and cup volume, and decreased rim area have been reported in patients with Alzheimer's compared to healthy controls. 5 , 41 …”
Section: Discussionmentioning
confidence: 98%
“…However, in studies of patients with MS, the optic nerve has been described to appear pale and atrophied, and patients with Parkinson's have been shown to have shallower cups compared to healthy controls. 39 , 40 Additionally, optic nerve pallor, increased CDR and cup volume, and decreased rim area have been reported in patients with Alzheimer's compared to healthy controls. 5 , 41 …”
Section: Discussionmentioning
confidence: 98%
“…A. OCT Many studies have suggested OCT as a useful tool for detecting progression in patients with MS but not in PPMS patients [36], compared with controls Lower ganglion cellinner plexiform layer (GCIPL), peripapillary retinal nerve fiber layer (pRNFL), and total macular volume (TMV) was found in patients with SPMS compared to RRMS [37]- [43] and is a beneficial tool to monitor the disability progression [38]. This shows that Longitudinal assessment of retinal thinning could confirm those patients who converted to SPMS.…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…Recent studies demonstrate conflicting data about the main focus of RNFL thinning. Depending on the cohort, temporal and nasal quadrants are most affected [ 28 , 29 ]. Furthermore, progressive thinning of the retinal ganglion cell (RGC) and the inner plexiform layer has also been described for relapsing–remitting MS (RRMS) [ 29 ].…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…Disease progression without a relapse, typical for primary progressive (PPMS) or secondary progressive MS (SPMS), is also associated with increased GCIPL and pRNFL thickness loss [ 40 ]. This could, to a certain extent, explain why progressive MS patients show faster annual pRNFL and GCIPL thinning and lower values at baseline compared to RRMS [ 28 , 41 43 ]. As mentioned before, GCIPL and pRNFL can be correlated with brain atrophy and spinal cord atrophy, cortical lesion volume, and leptomeningeal enhancement [ 44 48 ].…”
Section: Optical Coherence Tomographymentioning
confidence: 99%